Pendidikan Islam Moderat Kelompok Islam Transnasional; Critical Pedagogy pada Pola Pendidikan Jama’ah Tabligh di Indonesia - Abdul Malik (Departement of Mathematics Education, 2022)
This paper attempts to explore the values of moderate Islamic education held by the Jama'ah Tabligh group. In general, the preaching movement of Jama'ah Tabligh has significantly impacted social transformation in Muslim society. Since its Abstractpresence in mainland India several decades ago, the Jama'ah Tablgih missionary movement has expanded across continents and countries all over the world with millions of followers spread across various regions including Indonesia. Since the issue of global terrorism emerged, the Jamaah Tabligh movement has received increasing attention in Islamic studies. Given that the group is suspected of being a transnational Islamic group movement advocating exclusivist religious narratives. Therefore, this study’s question is whether the Jama'ah Tabligh movement promotes religious radicalism or moderation. If religious moderation is developed, then how is the moderation of Islamic education from the perspective of the Tablighi Jama'ah? This research was carried out through field research with a qualitative approach through data collection techniques of participant observation, in-depth interviews, and documentation involving more than twenty informants spread across ten locations on the island of Lombok, West Nusa Tenggara. The results of the study show that the Jama'ah Tablighi group movement has encouraged changes in individual and group religious understanding to become more inclusive in a short time. These changes occur through non-formal and informal Islamic education.